Collar rot of passion fruit caused by Rhizoctonia solani and its control - and M.M. GANAPATHY, INDU S. SAWANT, S.D. SAWANT (Indian Phytopathology, 2002)
Severe incidence of collar rot and wilting was observed on 4-year old passion fruit vines of the variety Purple (Passiflora edulis f. edulis Sims.), and a hybrid between purple and yellow named ’Kavery’ which is reported to be resistant to Fusarium wilt. During 1986-87, the total mortality recorded was 15.3%. The following year mortality was 4.2% but the number of vines exhibiting collar rot symptoms had increased from 6.9% in January 1987 to 45,8% in January 1988. The length of the infected area ranged from 5 to 34 cm from the collar with an average length of 16 cm. All the wilted vines exhibited 0.5-1.5 cm deep cracking of the infected tissues at the collar region (Fig, 1). Experiments were conducted to identify the causal organism and to find suitable control measures for the disease.